(untitled) (Studia Prawnicze / The Legal Studies, 1982)
Limitations of the employee’s time-off invoke considerations of legal, philosophical and psychological character. Time off is a sign of human right to freedom limited in employment relationships by an idea of common goods. It is also connected with the principle of freedom of work. In existing social structures there is an antynomy between freedom and work. In result, there is a contradiction between hours of work and time off. Solution of this contradiction does not lie in shortening hours of work but in adjusting them to the rhythm of personal life of a man. In a possibly largest degree we should leave aside stiffened discipline of hours of work in favour of discipline of executing given tasks, which gives the employees relatively wider freedom as to the method, place and time of executing tasks. Considering highly time-consuming character of out-of-work activities, this is the only possible way of lessening the pressure on shortening hours of work, so costly from economic point of view. The principle of freedom of work should be construed more widely. Besides entering into employment relationship this includes also changing and dissolving it. This results from article 8 para 2 and 3/III of the Pact of Citizen’s Rights and from article 2 para 1 and 2 (b, d) of ILO convention nr 29. Therefore article 11 of the labour code should obtain extensive interpretation. In relation to “specific needs of the work establishment” other than rescue operations or breakdown, provisions limiting employee’s right to time off, and especially article 133 para 1 are ius dispositivum. For work limiting employee’s time off his consent is necessary. Rescue operations breakdown and “other specific needs of an establishment” are future and uncertain events. So is possible collision between the limitation of employee’s time off and his socially motivated interest. All these events constitute sui generis system of conditions to which article 89 in connection with article 300 of labour code are to be applied respectively. They are functionally and legally bound. Realization of the condition on the part of the establishment results in creation of employee’s duty, unless theafore-mentioned collision with his interest arises.